Hyperon-Nuclear Interactions From SU(3) Chiral Effective Field Theory - Petschauer, Stefan; Haidenbauer, Johann; Kaiser, Norbert; Meißner, Ulf-G.; Weise, Wolfram (Frontiers in Physics, 2020)
The interaction between hyperons and nucleons has a wide range of applications in strangeness nuclear physics and is a topic of continuing great interest. These interactions are not only important for hyperon-nucleon scattering but also essential as basic input to studies of hyperon-nuclear few- and many-body systems including hypernuclei and neutron star matter. We review the systematic derivation and construction of such baryonic forces from the symmetries of quantum chromodynamics within non-relativistic SU(3) chiral effective field theory. Several applications of the resulting potentials are presented for topics of current interest in strangeness nuclear physics.